Distinct Embryonic Origin and Injury Response of Resident Stem Cells in Craniofacial Muscles - Cheng, Xu; Shi, Bing; Li, Jingtao (Frontiers in Physiology, 2021)
Craniofacial muscles emerge as a developmental novelty during the evolution from invertebrates to vertebrates, facilitating diversified modes of predation, feeding and communication. In contrast to the well-studied limb muscles, knowledge about craniofacial muscle stem cell biology has only recently starts to be gathered. Craniofacial muscles are distinct from their counterparts in other regions in terms of both their embryonic origin and their injury response. Compared with somite-derived limb muscles, pharyngeal arch-derived craniofacial muscles demonstrate delayed myofiber reconstitution and prolonged fibrosis during repair. The regeneration of muscle is orchestrated by a blended source of stem/progenitor cells, including myogenic muscle satellite cells (MuSCs), mesenchymal fibro-adipogenic progenitors (FAPs) and other interstitial progenitors. Limb muscles host MuSCs of the Pax3 lineage, and FAPs from the mesoderm, while craniofacial muscles have MuSCs of the Mesp1 lineage and FAPs from the ectoderm-derived neural crest. Both in vivo and in vitro data revealed distinct patterns of proliferation and differentiation in these craniofacial muscle stem/progenitor cells. Additionally, the proportion of cells of different embryonic origins changes throughout postnatal development in the craniofacial muscles, creating a more dynamic niche environment than in other muscles. In-depth comparative studies of the stem cell biology of craniofacial and limb muscles might inspire the development of novel therapeutics to improve the management of myopathic diseases. Based on the most up-to-date literature, we delineated the pivotal cell populations regulating craniofacial muscle repair and identified clues that might elucidate the distinct embryonic origin and injury response in craniofacial muscle cells.